International law and humanitarian intervention - Savić Sava (Međunarodni Problemi)
Taking an action by the international community, individual states or their organizations with the aim of protecting citizens in some country from the tyranny of their own authorities has been defined as a humanitarian intervention. According to international law the use of power as an instrument in international relations is, however, prohibited and therefore, any approach to humanitarian intervention is stretched out between the challenges of moral responsibility and limitations of legislature. The subject of discussion in this article is the legislative aspect of humanitarian intervention by force. The research is focused on law and legitimating of humanitarian intervention by force without the United Nations Security Council approval. .